Total liver graft implantation procedures in orthotopic pig transplantation - Brito, Marcus Vinicius Henriques (2010)
Purposes: To report procedures in receptor animal of hepatectomy and total liver graft implantation in pig orthotopic transplantation. Methods: Fourteen female pigs Sus escrofa domesticus were utilized, weighing between 5 and 8 kg, which were distributed in 2 groups: donors and receptors, being only the last ones considered in the result of this research. In order to initiate the surgery, animals were previously anesthetized and placed under transoperative monitoring, being immediately submitted to the necessary procedures for the hepatectomy of the receptor and total graft implantation. Results: The mean times of anhepatic stages and receptor surgery were 64.6 and 142.6 minutes. Conclusion: The reported techniques of hepatectomy in the receptor animal and total implantation of the graft are feasible, effective and reproducible, enabling the training of professionals and medical students, as well as the development of further researches involving liver transplantation.